The geriatric management of frailty as paradigm of “The end of the disease era” - Cesari, Matteo; Marzetti, Emanuele; Thiem, Ulrich; Pérez-Zepeda, Mario Ulises; Abellan Van Kan, Gabor; Landi, Francesco; Petrovic, Mirko; Cherubini, Antonio; Bernabei, Roberto (European journal of internal medicine, 2016)
The sustainability of healthcare systems worldwide is threatened by the absolute and relative increase in the number of older persons. The traditional models of care (largely based on a disease-centered approach) are inadequate for a clinical world dominated by older individuals with multiple (chronic) comorbidities and mutually interacting syndromes. There is the need to shift the center of the medical intervention from the disease to the biological age of the individual. Thus, multiple medical specialties have started looking with some interest at concepts of geriatric medicine in order to better face the increased complexity (due to age-related conditions) of their average patient. In this scenario, special interest has been given to frailty, a condition characterized by the reduction of the individual's homeostatic reserves and increased vulnerability to stressors. Frailty may indeed represent the fulcrum to lever for reshaping the healthcare systems in order to make them more responsive to new clinical needs. However, the dissemination of the frailty concept across medical specialties requires a parallel and careful consideration around the currently undervalued role of geriatricians in our daily practice. •New models of care are needed for addressing the complex needs of frail elders.•Geriatric concepts (as frailty) are growingly adopted by other medical specialties.•Integrated care centered on the geriatrician is needed for managing frail elders.•Geriatricians must enforce respect for their role, background, and capacities.•Underestimating the geriatrician's role in an aging world is clearly paradoxical.